1995
DOI: 10.1080/01448765.1995.9754736
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Understanding the Molecular Genetics and Biochemistry of Calcium Phosphate Solubilization by Gram Negative Bacteria

Abstract: For most of this century agricultural microbiologists and microbial ecologists have been interested in the ability of some bacteria to efficiently dissolve "insoluble" calcium phosphates. This phenotype has been termed mineral phosphate solubilizing (Mps). This minireview discusses recent work suggesting that the direct oxidation pathway for glucose dissimilation forms the metabolic basis for the strongly Mps+ phenotype observed in many species of gram negative bacteria. In the past, the physiological signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(200 citation statements)
references
References 14 publications
7
182
0
11
Order By: Relevance
“…Phosphate-solubilizing microorganisms, in addition to provide phosphorus for plants, provide growth promoting substances like hormones, vitamins and amino acids. It is reported that mechanism of solubilizing phosphate is associated with release of low molecular weight organic acids which chelate the cation bound to phosphate and convert it into soluble form 16,24,25 . According to our result from phosphate solubilizing ability of studied bacteria on NBRIP medium, almost all of them could solubilize phosphate but in different amount.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate-solubilizing microorganisms, in addition to provide phosphorus for plants, provide growth promoting substances like hormones, vitamins and amino acids. It is reported that mechanism of solubilizing phosphate is associated with release of low molecular weight organic acids which chelate the cation bound to phosphate and convert it into soluble form 16,24,25 . According to our result from phosphate solubilizing ability of studied bacteria on NBRIP medium, almost all of them could solubilize phosphate but in different amount.…”
Section: Discussionmentioning
confidence: 99%
“…In Gram-negative bacteria this mineral phosphate solubilization (MPS) phenotype is attributed predominantly to the secretion of low molecular weight organic acids such as gluconic and 2-ketogluconic acids in the periplasmic space 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Acidification is a key step in the dissolution of many poorly soluble mineral phosphates, and hence, as proposed by Goldstein (1996), the direct oxidation of glucose to gluconic acid is a key step in some of the major mechanisms for MPS in Gram-negative bacteria, which are suggested to be more efficient at MPS than Gram-positive bacteria owing to secretion of organic acids from sugar metabolism (Sashidhar & Podile, 2009). The pathway is mediated by a membrane-bound glucose dehydrogenase and requires pyrroloquinoline quinone (PQQ) as a cofactor (Goldstein, 1995). Bacteria belonging to the genera Achromobacter, Agrobacterium, Bacillus, Enterobacter, Erwinia, Escherichia, Flavobacterium, Mycobacterium, Pseudomonas and Serratia have been found to be efficient in phosphate solubilization (Goldstein, 2001).…”
Section: Functional Gene Composition and Key Enzymesmentioning
confidence: 99%